Adolescents' Use of Combined Hormonal Contraceptives for Menstrual Cycle–Related Problem Treatment and Contraception: Evidence of Potential Lifelong Negative Reproductive and Bone Effects. Issue 2 (3rd May 2016) - Prior, Jerilynn C.
Abstract : Non-sexually active adolescents are currently treated with combined hormonal contraception (CHC) for common experiences (e.g., cramps, acne) and serious problems (e.g., hypothalamic amenorrhea, heavy menstrual flow) for which it is not indicated, is ineffective, and is likely to cause negative long-term reproductive and bone effects. The importance to a woman's health of adolescent reproductive/bone maturation is described. Evidence is also provided to show the association of CHC use by adolescents with subfertility and inadequate bone growth. Ibuprofen is safer and more effective for cramps and heavy flow; cyclic progesterone builds bone in amenorrhea. In summary, a common, unscientific medical "habit" is compromising long-term reproductive and bone health in adolescents.